The Cretaceous world: plate tectonics, palaeogeography and palaeoclimate - Scotese, Christopher R.; Vérard, Christian; Burgener, Landon; Elling, Reece P.; Kocsis, Ádám (Geological Society of London, 2025)
The tectonics, geography and climate of the Cretaceous world were very different from the modern world. At the start of the Cretaceous, the supercontinent of Pangaea had just begun to break apart and only a few small ocean basins separated Laurasia, West Gondwana and East Gondwana. Unlike the modern world, there were no significant continent–continent collisions during the Cretaceous, and the continents were low-lying and easily flooded. The transition from a Pangaea-like configuration to a more dispersed continental arrangement had important effects on the global sea level and climate. During the Early Cretaceous, as the continents rifted apart, the new continental rifts were transformed into young ocean basins. The oceanic lithosphere in these young ocean basins was thermally elevated, which boosted sea level. Sea level, on average, was c. 70 m higher than that of the present day. Sea level was highest during the mid-Cretaceous (90–80 Ma), with a subsidiary peak occurring c. 120 Myr ago (early Aptian). Overall, the Cretaceous was much warmer than the present-day climate (>10°C warmer). These very warm times produced oceanic anoxic events (OAEs), and the high temperatures in equatorial regions sometimes made terrestrial and shallow-marine ecosystems uninhabitable (temperatures >40°C). This is unlike anything we have seen in the last 35 Myr and may presage the eventual results of man-made global warming. This mostly stable, hot climate regime endured for nearly 80 Myr before dramatically terminating with the Chicxulub bolide impact 66 Myr ago. Temperatures plummeted to icehouse levels in the ‘impact winter’ as a result of sunlight-absorbing dust and aerosols being thrown into the atmosphere. As a consequence of the collapse of the food chain, c. 75% of all species were wiped out. The effect of this extinction event on global ecosystems was second only to the great Permo-Triassic Extinction.
CRIS-Team Scopus Importer:2025-04-04